2021
DOI: 10.3390/life11121329
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Microbiota Is Significantly Less Diverse in Patients with Chronic Spontaneous Urticaria Compared to Healthy Controls: Preliminary Results

Abstract: Background: Because of the important role in regulating the immune system, increasing evidence suggests a possible implication of gut microbiota in Chronic spontaneous urticaria (CSU). Although the oral cavity is the first site of contact between microbiota and the immune system, the association between salivary microbiota and CSU has not yet been reported. Objective: This case-control study aimed to compare differences in salivary microbiota between CSU patients and healthy controls (HC). Twenty-three partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Treg cells can suppress pro-inflammatory cytokines mediated by various T-cells, including Th2 cells, and can induce the secretion of anti-inflammatory mediators, thereby reducing inflammation [ 14 ]. Reduced Treg cells have been observed in patients with CSU [ 64 , 65 , 66 ]. GPCRs are also expressed in mast cells, the key cells in the development of urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells can suppress pro-inflammatory cytokines mediated by various T-cells, including Th2 cells, and can induce the secretion of anti-inflammatory mediators, thereby reducing inflammation [ 14 ]. Reduced Treg cells have been observed in patients with CSU [ 64 , 65 , 66 ]. GPCRs are also expressed in mast cells, the key cells in the development of urticaria.…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on previous research that found that the combination of the two above-mentioned probiotics may reduce the release of pro-Th-2 cytokines from THP-1 cells, favouring an improvement in Th1/Th2 [ 87 ]. Therefore, it should be mentioned that some Bifidobacterium species have useful anti-inflammatory effects; some strains (used as probiotics) improve dysbiosis and alleviate the inflammatory response, possibly by/through inducing Treg cells with their anti-inflammatory mediators [ 88 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Increasing evidence suggested that changes in the gut microbiome can trigger skin inflammation ( Kim et al, 2020 ; Chun et al, 2021 ). It was worth noting that the 16S ribosomal RNA gene sequencing results showed that microbial composition was significantly different between urticaria patients and healthy individuals ( Lu et al, 2019 ; Ćesić et al, 2021 ; Wang et al, 2021 ; Zhang et al, 2021 ). Besides, a randomized placebo-controlled trial suggested adjunct therapy with probiotics was safe and effective at four weeks in treating chronic urticaria in children ( Bi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%